Trajectories of Teacher-Student Warmth and Conflict at the Transition to Middle School: Effects on Academic Engagement and Achievement - Hughes, Jan N. (J Sch Psychol, 2017)
Using piece-wise longitudinal trajectory analysis, this study investigated trajectories of teacher-reported warmth and conflict in their relationships with students 4 years prior to and 3 years following the transition to middle school in a sample of 550 academically at–risk and ethnically diverse adolescents. At the transition to middle school, teacher reports of warmth showed a significant drop (shift in intercept), above age-related declines. Both warmth and conflict declined across the middle school years. Structural equation modeling (SEM) tested effects of the shifts in intercept and the post-transition slopes on reading and math achievement, teacher-rated engagement, and student-reported school belonging 3 years post-transition, above pre-transition levels of the outcome. For warmth, a drop in intercept predicted lower math scores and engagement, and a more positive slope predicted higher engagement. For conflict, an increase in intercept and a negative slope predicted lower engagement. Implications of findings for reducing normative declines in academic engagement in middle school are discussed.